ChemInform Abstract: Decatungstate Photocatalyzed Acylations and Alkylations in Flow via Hydrogen Atom Transfer. Issue 13 (March 2016) - Bonassi, Filippo; Ravelli, Davide; Protti, Stefano; Fagnoni, Maurizio
Abstract: These photocatalyzed radical conjugate addition reactions are carried out in a meso‐scale flow photoreactor consisting in coils of UV‐transparent FEP tubing wrapped around a water‐cooled medium pressure mercury vapor lamp.